The Effect of Teachers’ Use of L1 on EFL Learners’ Anxiety and Enjoyment in Emergency Online Language Classrooms - Reza Bakhsheshi Atigh; Mohammad Mohammadi; Salva Kazemipour Khabbazi (Research in English Language Pedagogy, 2023)
Emergency online teaching and learning due to the COVID-19 pandemic has called for new research. The pandemic situation has increased the importance of creating a low-anxiety atmosphere and enhancing learners’ enjoyment levels. As a result, this study aimed to investigate the level of language learners’ emotions; that is, foreign language enjoyment (FLE) and foreign language classroom anxiety (FLCA) in online education together with the effect of teachers’ L1 use on these two effects. Participants were 81 intermediate English as a foreign language (EFL) learners in four intact classes, in two of which the teacher used both their first language (L1) and English, while in the other two, he only used English as the medium of instruction. They then completed a questionnaire, consisting of two parts, one designed by Horwitz et al. (1986) and the other one by Dewaele and MacIntyre (2014), which reveal the levels of FLCA and FLE, respectively. The paired t-test indicated higher levels of FLE compared to FLCA reported by the participants. The correlation analysis pointed to a significant negative correlation between FLE and FLCA, implying that as enjoyment increases, anxiety level decreases. Furthermore, according to the independent t-test, learners in both groups reported similar levels of FLE and FLCA. Thus, it could be concluded that teachers’ use of L1 did not affect the levels of FLE and FLCA in online education. The current study provides significant pedagogical implications for EFL practitioners.